Analysis of Standard Implementation Factors Micro Entity Financial Accounting Small Medium Enterprise (SAK EMKM) - Irfan, Irfan (Economic: Journal Economic and Business, 2025)
The purpose of this study is to determine and analyze the influence of accounting understanding directly on the implementation of SAK EMKM and the influence of education level directly on the implementation of SAK EMKM. This study uses a quantitative associative research type with a sample of 60 respondents who are MSME owners in Medan City, especially in Medan Perjuangan District. Data collection techniques use a list of statements such as questionnaires and data analysis techniques use Partial Least Square (SmartPLS). The results of the study indicate that there is a positive and significant influence of accounting understanding on the implementation of SAK EMKM and the results of the study indicate that there is a positive and significant influence of education level on the implementation of SAK EMKM.